Web-based claim management system - Yoong Ying Khai (School of Microelectronics, University Malaysia Perlis, 2015)
The project title for this thesis is Web-based claim management system for Department of Electronic Engineering Technology of Faculty of Engineering Technology. This project is to develop a web-based claim management system that allows the staff to apply travel claim through online. This system is using PHP programming languages and uses the MySQL for the database. In order to make the system can connect to the database, the researcher had installed XAMPP that contains Phpmyadmin for managing the database, Apache server and can make the interface to interact with the database using MySQL Statements and PHP. There are three main modules for this system which is staffs registration, claim request, and claim approval.